Utilization of Smart Apps Creator (SAC) as a Learning Media for Social Studies - Armilah, Ilah; Sinaga, Risma M; Istiawati, Novia Fitri; Maydiantoro, Albet; Adha, M. Mona (International Journal of Educational and Psychological Sciences, 2024)
The use of Smart Apps Creator as a learning media, especially in social studies subjects, has produced products that have been validated by material and media experts with a score of 81.82% from material experts and 84% from media experts, indicating that the developed product is very feasible to use in learning activities. Meanwhile, the assessment according to users, namely students and educators, is 85.6% and 90.2% respectively with the criteria of very feasible/very practical/very easy.